Pleasure, provocation and value in hospital art: The evaluation of the University College London Hospitals arts programme. (23rd August 2012) - Froggett, Lynn; Little, Robert
This article discusses a psychosocial study of a hospital arts programme informed by the principles of 'realistic evaluation', which assumes that individuals' responses to artworks reflect their circumstances and are influenced by social context. The methodology combined experience-distant and experience-near methods – an observation scale and elicitation of views and perceptions. The findings are discussed in relation to a model of public value, widely debated in the cultural sector, that distinguishes intrinsic, institutional and instrumental dimensions. It is argued that intrinsic value enables institutional value to be fully realized in that it enables people to make personally meaningful use of artworks that at the same time create a sense of connection to the institution as a community. However, since intrinsically good art may also challenge some people, this raises the question of what kind of provocation is acceptable in health-care contexts.